2016
DOI: 10.1179/1362171815y.0000000059
|View full text |Cite
|
Sign up to set email alerts
|

Review: magnetically assisted resistance spot welding

Abstract: Currently, the use of advanced high strength steels (AHSSs) is the most cost effective means of reducing vehicle body weight and maintaining structural integrity at the same time. However, AHSSs present a big challenge to the traditional resistance spot welding (RSW) widely applied in automotive industries because the rapid heating and cooling procedures during RSW produce hardened weld microstructures, which lower the ductility and fatigue properties of welded joints and raise the probability of interfacial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
(75 reference statements)
1
21
0
Order By: Relevance
“…It can be seen that the weld nugget produced under the action of EMS (EMS weld) becomes larger and thinner than the traditional resistance spot weld. This is consistent with the results from earlier studies [11][12][13] showing that the EMS drives the molten metal in the nugget to flow clockwise and generates a centrifugal movement, which will promote the growth of the nugget in a radial direction.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It can be seen that the weld nugget produced under the action of EMS (EMS weld) becomes larger and thinner than the traditional resistance spot weld. This is consistent with the results from earlier studies [11][12][13] showing that the EMS drives the molten metal in the nugget to flow clockwise and generates a centrifugal movement, which will promote the growth of the nugget in a radial direction.…”
Section: Resultssupporting
confidence: 93%
“…Shen et al have found that EMS could refine the grain structure, increase the weld nugget diameter, reduce the risk of shrinkage cavities, and improve the mechanical properties of the joint in RSW of advanced high-strength steel DP590 [8] and DP780 [9,10]. Li et al have studied the effect of EMS upon the nugget formation of DP980 steel and they found that, under the action of EMS, the nugget symmetry improved and the macrocrystallization direction in the fusion became less obvious [11]. Li et al have investigated the effect of EMS upon resistance spot welds of 5052 aluminum alloy, and suggested that the effect of EMS was more sensitive to the change of welding time and was insensitive to the change of electrode force [12].…”
Section: Introductionmentioning
confidence: 96%
“…Li et al. [ 22 ] observed the consequence of the EMF in many welding processes for weld arc stability and weld pool behaviors. Li et al.…”
Section: Trends and Advancements In Emf-assisted Welding-processmentioning
confidence: 99%
“…To further improve the welding quality of the joint, in recent years, numerous scholars have developed various welding‐assisted methods. For instance, magnetic field‐assisted, [ 1 ] ultrasonic‐assisted, [ 2,3 ] induction heating‐assisted, [ 4,5 ] laser‐assisted, [ 6,7 ] vibration‐assisted, [ 8,9 ] and arc‐assisted laser welding [ 10 ] (LW) are applied. The magnetic field‐assisted welding method, in particular, has garnered a lot of attention and interest because of its simple components, low cost, and effective weld formation.…”
Section: Introductionmentioning
confidence: 99%